2011
DOI: 10.1080/17588928.2010.525627
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of somatosensory perception by motor intention

Abstract: The intention to execute a movement can modulate our perception of sensory events; however, theoretical accounts of these effects, and also empirical data, are often contradictory. We investigated how perception of a somatosensory stimulus differed according to whether it was delivered to a limb being prepared for movement or to a nonmoving limb. Our results demonstrate that individuals perceive a somatosensory stimulus delivered to the "moving" limb as occurring significantly later than when an identical stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 25 publications
(45 reference statements)
6
26
0
Order By: Relevance
“…A recent study (Parkinson et al. ) reports data that were consistent with our contention that movement planning attenuates tactile perception. Parkinson et al.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study (Parkinson et al. ) reports data that were consistent with our contention that movement planning attenuates tactile perception. Parkinson et al.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this view, recent functional brain-imaging studies have demonstrated that punctate somatosensory stimulation of the upper limbs produces significant increases in brain activity--blood oxygen level-dependent (BOLD) response)--bilaterally within the insular cortex (e.g., Jackson, Parkinson, Pears, & Nam, 2011;Parkinson et al, 2011). However, neurophysiological studies suggest that the insular cortex may play a particularly important role in representing the emotional significance of somatosensory signals.…”
Section: Functional Anatomy Of Tics In Tsmentioning
confidence: 71%
“…This phenomenon is typically called gating or suppression of the sensory input. It was explained by the reduction of somatosensory evoked potentials (Rushton et al 1981;Duysens et al 1995;Staines et al 2000;Seki and Fetz 2012), increase in electrocutaneous detection thresholds (Angel and Malenka 1982;Chapman et al 1987;Williams et al 1998;Chapman 2000, 2002), reduction of the spike responses in first-order interneurons (Seki et al 2003), and decrease in BOLD (bloodoxygen-level-dependent) signal during fMRI (functional magnetic resonance imaging) (Parkinson et al 2011). Rushton et al (1981) showed early on that secondary evoked potentials are suppressed with both active and passive movement, in which the participants moved their fingers against constant force or their fingers were moved by a motor, respectively, at constant speed.…”
Section: Introductionmentioning
confidence: 98%